Transforming Medical Healthcare through Research: Introduction - Abdul Rahim, Roslina (IIUM Press, 2023)
On the 11th of March 2020, the World Health Organisation officially categorised the COVID-19 outbreak as pandemic. The global impact of this announcement was not only on the world economy but also the academic sector. Many researchers were unable to conduct or continue their research during that time. As the pandemic evolved into a new normal, slowly but gradually movement restrictions were lifted, new standard operation procedures were adopted allowing researchers to return to their area of study. In 2020, even the much-celebrated Kulliyyah of Medicine annual research event was postponed. In 2021, the conference named as ‘Virtual Medical Research Symposium (MRS) 2021’ managed to be held adhering to the COVID-19 restrictions at the time. The theme was ‘Medical Research during the Pandemic: Adapting and Innovating in Adversity. The symposium received participation from numerous basic medical sciences and clinical research and case series. All these researchers shared their findings and innovations from research conducted during the pandemic. At the end of the symposium, the MRS participants were invited to contribute to the inaugural research book project. The aim of this project is to increase the number of publications particularly research book chapters in the “Transforming medical healthcare through research” our first research book, simultaneously contributing to Kulliyyah of Medicine's Malaysia Research Assessment (MyRA) performance.